COVID-19 TRIGGERED TECHNOLOGY INTEGRATION STRATEGIES FOR ENHANCED STUDENT ENGAGEMENT IN BLENDED LEARNING - Sibanda, Timothy; Josua, Lukas (African Journal of Education and Practice, 2022)
Purpose: This study reflects on three technology integration strategies for enhanced student engagement, namely; keeping the learning social, keeping the learning authentic, and ensuring that the technology adds value to learning. Methodology: The study employed a student technology profiling survey involving 3rd Year Cell Molecular Biology, Microbiology and Genetics students at the University of Namibia in 2021. The survey used a Google Document whose link was distributed to students through class WhatsApp group. Further, literature is reviewed on student engagement, and blended learning. The data was qualitatively presented using graphs. Findings: The study revealed that keeping the learning social ensures learning from sociocultural perspectives, and allows for social constructivist methods of learning while the adoption of authentic learning as a pedagogical model can help to better prepare students for professional practice. Teachers can ensure that technology integration adds value by using instructional strategies that stimulate students into engaging with higher-level cognitive skills and differentiated learning. The study found that based on the nature of the course under review, we identified the Flipped Classroom model and the Enriched-Virtual model is most appropriate blended learning modes for full-time students and distance students, respectively. Unique contribution to theory, practice and policy: It is recommended that higher education institutions should consider redesigning their curriculum policies in order to integrate blended learning in all their courses in order to improve the quality of education, enhance student learning and engagement, as well as overall quality of the university graduates.